A practical individualized radiation precaution based on the dose rate at release time after inpatient 131I ablation therapy. - Sangwon Han (Public Library of Science (PLoS), 2021)
Introduction Retained radioactivity of 131I after ablation therapy largely differs in each patient according to factors including the amount of remnant thyroid tissue, renal function, and use of recombinant human thyroid-stimulating hormone. To reduce unnecessary restriction of patient's daily life after inpatient 131I ablation therapy, we propose a practical individualized method for radiation precaution based on dose rate at release time. Methods We evaluated 215 patients with differentiated thyroid cancer who underwent inpatient 131I ablation therapy following total thyroidectomy. Effective dose equivalent rates at 1-m distance were measured upon release (EDRR) on day 2 and during delayed whole-body scan (EDRD) visits on day 6‒8 after 131I administration. The biexponential model was designed to estimate total effective dose equivalent to others. To assess conservativeness of our model, EDRD estimated by our model was compared with measured EDRD. EDRR-based periods of precaution not to receiving 1 mSv of radiation exposure were estimated and compared with those based on administered radioactivities on American Thyroid Association (ATA) recommendations. Results The EDRR ranged from 1.0-48.9 μSv/hr. The measured EDRD were equal to or lower than estimated EDRD in all patients, except for one, indicating that our model is sufficiently conservative. According to our model, no subjects needed additional daytime restriction after release. The maximum permissible times for public transportation use were longer in all patients compared with those based on administered radioactivities. Nighttime restriction periods were significantly shorter than those based on administered radioactivity; median periods requiring sleeping apart were 0 (range, 0‒5), 4 (range, 1‒14), and 3 (range, 2‒13) days after release in patients treated with radioactivity doses of 2.96, 5.50, and 7.40 GBq, respectively, needing 8, 16, and 19 additional days, respectively, based on administered radioactivity. Conclusions Radiation safety instructions using proposed method based on EDRR of individual patient could safely reduce the burden of radiation precaution.